Searches for the Σ-nucleus Potential - Petridou, Th. (HNPS Advances in Nuclear Physics, 2020)
The determination of the Σ-nucleus potential is the main orientation of the late Σ-hypernuclear physics. For this purpose, the last (Κ-,π+) light Σ-hypernuclear spectra were studied together with the recent (π-, Κ+)28Si_Σ spectrum in the context of the Green function method with a square well optical potential and a delta function spin-orbit interaction using plane waves. It was found that these spectra with a broad enhancement mainly at large energies are well described by a repulsive potential with nonzero imaginary and spin-orbit parts.